2018
DOI: 10.1093/nar/gky171
|View full text |Cite
|
Sign up to set email alerts
|

Designer epigenome modifiers enable robust and sustained gene silencing in clinically relevant human cells

Abstract: Targeted modulation of gene expression represents a valuable approach to understand the mechanisms governing gene regulation. In a therapeutic context, it can be exploited to selectively modify the aberrant expression of a disease-causing gene or to provide the target cells with a new function. Here, we have established a novel platform for achieving precision epigenome editing using designer epigenome modifiers (DEMs). DEMs combine in a single molecule a DNA binding domain based on highly specific transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 41 publications
3
69
1
Order By: Relevance
“…The “hit and run” hypothesis has been proposed several times, but primarily in the context of transcriptional activation . There is, however, also a growing interest in epigenetic co‐repressors, both natural and artificial, that operate via “hit and run” mechanisms . We suggest that the “hit and run” mechanism is perhaps most prevalent in transcriptional repression.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The “hit and run” hypothesis has been proposed several times, but primarily in the context of transcriptional activation . There is, however, also a growing interest in epigenetic co‐repressors, both natural and artificial, that operate via “hit and run” mechanisms . We suggest that the “hit and run” mechanism is perhaps most prevalent in transcriptional repression.…”
Section: Discussionmentioning
confidence: 85%
“…Further, the idea of “hit and run” and stable repression has been used as a tool to achieve targeted gene silencing. Artificial DNA‐binding domains (transcription activator‐like effectors [TALEs] and dCas9) have been fused to histone‐modifying enzymes requiring only transient expression for stable and inheritable gene silencing . In some cases, it may be that the jailer's key can be thrown away and life‐long gene repression ensues.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, TALE domain was fused to the LSD1 histone demethylase for downregulation of proximal genes by removing enhancer-associated chromatin modifications from target loci (Mendenhall et al 2013). TALE domain has also been fused to the DNMT3A-Dnmt3L for stably silencing target gene expression by inducing DNA methylation and reducing chromatin accessibility at the promoters (Mlambo et al 2018). In addition, the use of light-sensitive heterodimerizing proteins CRY2 and CIB1 enabled optogenetic control of epigenome editing.…”
Section: Recent Advances In Aav Delivery Of Crispr Fusion Proteinmentioning
confidence: 99%
“…Our recent examination showed that reprogramming into induced pluripotent stem cells could be achieved by adding only one recombinant platinum TALE protein fused with a transcriptional activation domain and cell‐penetrating peptide . Similarly, another group showed that only one TALE with KRAB and DNA methyltransferase domains sufficiently suppressed the target gene in cultured cells . As the unintended global effect was observed in the dCas9‐epigenetic modifier, these techniques might be attractive alternatives, although comprehensive off‐target analysis must be carried out in TALE‐based systems as well as in dCas9‐based ones.…”
Section: A Closer Look At Front‐line Technologiesmentioning
confidence: 99%